Immune Dysregulation, Polyendocrinopathy, Enteropathy, X-Linked Syndrome Associated With a Novel Mutation of FOXP3 Gene - Agakidis, Charalampos; Agakidou, Eleni; Sarafidis, Kosmas; Papoulidis, Ioannis; Xinias, Ioannis; Farmaki, Evangelia (Frontiers in Pediatrics, 2019)
The immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare, x-linked, recessive disorder characterized by dysfunction of the T regulatory (Treg) lymphocytes leading to autoimmune diseases. Herein we report a male patient with IPEX syndrome who presented with severe diarrhea, eczema, and malabsorption leading to failure to thrive and necessitating total parenteral nutrition, as well as with liver dysfunction. Laboratory investigation showed elevated liver enzymes that declined following treatment with glucocorticosteroids and immunosuppressive drugs, marked eosinophilia, increased total IgE, and decreased Treg cells. DNA analysis revealed that the patient himself was hemizygous and his mother heterozygous for the exon 10, c.1015C>T (p.Pro339Ser) mutation of the FOXP3 gene, which has not been previously reported. The current case indicates that mutations resulting in substitution of a certain amino-acid (i.e. proline 339) by different amino-acids are manifested with different IPEX phenotypes.